Influences of polymorphism of packed particles on bulk characterizations in fluidization realm - Zhu, Quanhong; Cao, Yalong; Zhang, Qiang; Liu, Wankun; Guan, Hao; Liu, Donghui; Gai, Hengjun (Chinese journal of chemical engineering, 2024)
The characterization of a particle ensemble (rather than a single particle) is of paramount significance to various particle technologies and has long been a fundamental subject in the fluidization realm. However, many of such bulk characterizations as loosely-packed density (ρbl), minimum fluidization velocity (Umf), sphericity (φ), discharge rate through orifice (q), angle of repose (β), and segregation index (S), were found to be poorly reproducible, making the reported results seldom comparable. Since these bulk characterizations started from the packed state of particles, such poor reproducibility was ascribed to the polymorphism of packed particles in this work. We observed that in the fluidized bed, the settled/packed state of particles varied monotonously with the settling rate (α) from complete fluidization to zero. This phenomenon confirmed the polymorphic characteristic of packed particles and further enabled us to systematically disclose/clarify its influences on the aforementioned bulk characterizations. Such influences could be comprehensively and intuitively reflected by the impacts induced by α. With the decrease of α, ρbl, φ and q first increased, then decreased, and finally leveled off while Umf and β showed an opposite trend. On the other hand, S first increased and then remained invariant. As per these findings and definitions of these bulk characterizations, benchmarks were indicated to unify the selection of settled state among future scholars and further make their outcomes become fairly comparable. Additionally, most packed states of the particle ensemble were proved to be metastable with their formation and behavior being identical to those of the amorphous state. [Display omitted] •Effect of polymorphism of packed particles on bulk characterizations was explored.•Poor reproducibility of bulk characterizations resulted from such polymorphism.•Settled state of particles varied monotonously with the settling rate.•Benchmarks were proposed to unify choice of settled state among different scholars.•Most packed states of a particle ensemble were proved to be metastable.